Prothrombotic Changes in Hemostatic Parameters and C-reactive Protein in the Elderly with Winter Acute Respiratory Tract Infections - Horan, John T.; Francis, Charles W.; Falsey, Ann R.; Kolassa, John; Smith, Brian H.; Hall, William J. (Thrombosis and Haemostasis, 2001)
Mortality rates attributable to cerebrovascular and ischemic heart disease increase among older adults during the winter. Prothrombotic changes in the hemostatic system related to seasonal factors, such as ambient temperature changes, and winter acute respiratory tract infections, may contribute to this excess seasonal mortality. A prospective nested case-control study was conducted to assess the impact of winter acute respiratory tract infections on fibrinogen, factor VII, factor VIIa, D-dimer, prothrombin fragment 1.2, PAI-1, soluble P-selectin and C-reactive protein (CRP) in older adults. The change in laboratory parameters from baseline (fall) to the time of infection in both middle-aged and elderly individuals was compared with matched non-infected controls. In older adult participants with winter acute respiratory tract infections, significant increases occurred in fibrinogen and C-reactive protein, but not in any other markers. The mean fibrinogen increased 1.52 g/L (38%) and the mean CRP increased 37 mg/L (370%) over baseline (both p < 0.001). In a multivariate analysis, both infection and season were associated with the increase in fibrinogen, but only infection was associated with the CRP increase. Old age magnified the increase in CRP but not in fibrinogen. Winter acute respiratory tract infections induce an exaggerated inflammatory response in older adults. The associated increase in fibrinogen, an independent risk factor for ischemic heart disease, may be partly responsible for the excess winter vascular mortality.
Keywords: Respiratory tract infection; aged; stroke; ischemic heart disease; fibrinogen; C-reactive protein; season; hypercoagulability